2022
DOI: 10.3389/fncir.2022.916499
|View full text |Cite
|
Sign up to set email alerts
|

Basal Forebrain Impairment: Understanding the Mnemonic Function of the Septal Region Translates in Therapeutic Advances

Abstract: The basal forebrain is one of the three major brain circuits involved in episodic memory formation together with the hippocampus and the diencephalon. The dysfunction of each of these regions is known to cause anterograde amnesia. While the hippocampal pyramidal neurons are known to encode episodic information and the diencephalic structures are known to provide idiothetic information, the contribution of the basal forebrain to memory formation has been exclusively associated with septo-hippocampal cholinergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 264 publications
(311 reference statements)
0
7
0
Order By: Relevance
“…33,34 Our results in the TUG test (Figure 3B) and ISLT-Recognition (Figure 4), showing the most prominent treatment effect differences between plasma ptau181 strata, are instructive in that regard because both measures would be expected to be influenced by the cholinergic input from the medial septal nucleus of the basal forebrain to the hippocampus. 35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Our results in the TUG test (Figure 3B) and ISLT-Recognition (Figure 4), showing the most prominent treatment effect differences between plasma ptau181 strata, are instructive in that regard because both measures would be expected to be influenced by the cholinergic input from the medial septal nucleus of the basal forebrain to the hippocampus. 35…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Our results in the TUG test (Figure 3B) and ISLT-Recognition (Figure 4), showing the most prominent treatment effect differences between plasma ptau181 strata, are instructive in that regard because both measures would be expected to be influenced by the cholinergic input from the medial septal nucleus of the basal forebrain to the hippocampus. 35 Recently, the results similar to ours with respect to the association of a plasma biomarker of AD copathology on treatment response to a novel agent were reported 36 with the PDE9 inhibitor, irsenontrine; in a 12-week, placebo-controlled phase 2 study in DLB, "amyloid-negative" patients (evidenced by a high plasma Aβ42/40 ratio) demonstrated a trend (p = 0.053) toward improvement in cognition, measured using the Montreal Cognitive Assessment, whereas no such trends were evident in "amyloid-positive" patients. Together with our results, these findings point to the potential utility of a plasma biomarker for underlying pathology to decrease patient heterogeneity either as a covariate or by excluding patients with a concomitant, and potentially confounding, pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, both film excerpts targeting Sadness recreated scenarios of personal or social loss. Overall, the non-motor manifestations in this cluster suggest a predominant dysfunction of the cholinergic basal forebrain complex and its connected cortex, implicated in tender and sad affiliative feelings [59,98], sleep regulation [99], and, together with the hippocampus, in episodic memory formation [100]. In particular, successful memory performance has recently been shown to rely on strong functional connectivity between the BF and insular cortex, a core area of socioemotional processing [101].…”
Section: Plos Onementioning
confidence: 96%
“…The basal forebrain (BF) is a heterogenous region composed of multiple areas, including substantia innominate, nucleus accumbens and ventral pallidum of the basal ganglia, bed nucleus of the stria terminalis, the preoptic area, the nucleus basalis of Meynert, the septal nuclei and diagonal band of Broca ( Tsanov, 2022 ). Cholinergic, glutamatergic and GABAergic neurons are the major neuronal populations in the basal forebrain ( Xu et al, 2015 ).…”
Section: Basal Forebrainmentioning
confidence: 99%